Curcumin and omega-3 ameliorate experimental osteoarthritis progression in terms of joint pain and mitochondrial dysfunction - JooYeon Jhun; Donghwan Lee; Hyun Sik Na; Keun-Hyung Cho; Seung Yoon Lee; Jeong Su Lee; Young Joon Lee; Seok Jung Kim; Sung-Hwan Park; Mi-La Cho (Journal of Inflammation)
Abstract Background Osteoarthritis (OA), a chronic degenerative disorder, induces pain, joint inflammation, and destruction of the articular cartilage matrix. Curcumin and omega-3 have been used as dietary supplements for OA due to their anti-inflammatory and antioxidant properties. However, there is no evidence demonstrating a synergistic effect in OA. The current study aimed to investigate the therapeutic effects and underlying mechanism of a combination of curcumin and omega-3 in the treatment of OA. Methods Wistar rats were injected with monosodium iodoacetate to induce OA. Oral treatments of a vehicle, curcumin, curcumin and omega 3, or celecoxib were administered. Pain was analyzed according to the paw withdrawal latency, paw withdrawal threshold, and weight bearing ability. The joint was isolated from OA rats, and cartilage damage was evaluated using histomorphological techniques, the Mankin scoring system, and micro computed tomography analysis. Protein expression in the joint was examined using immunohistochemistry. The expression levels of catabolic markers were measured in curcumin and omega-3-treated OA chondrocytes. Results The OA animal model revealed diminished pain and cartilage conservation in response to the combined treatment. mRNA levels of matrix metalloproteinase 1 (MMP1), MMP3, and MMP13 were reduced in interleukin-1 beta-simulated human OA chondrocytes. Additionally, mitochondrial markers, cytochrome c oxidase 4, and TOMM20, were increased by the combination treatment. Conclusions These findings suggest promising therapeutic outcomes for the combined treatment of curcumin and omega-3 in OA patients.